Perpaduan Metode Debate dan Numbered Head Together terhadap Keaktifan Belajar dan Kepercayaan Diri Siswa pada Mata Pelajaran Pendidikan Agama Kristen - Ginting, Matius Timan Herdi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
In order for students to achieve the best learning outcomes, they must be involved in their studies and confident. Combining the debate method and the Number Head method together is one of the useful strategies to increase self-confidence and activity. If the Number Head Together method encourages students to actively participate in their education, the debate method seeks to develop students' self-confidence in voicing their opinions. The purpose of this study was to determine the difference in the influence of the experimental class and the control class. The Independent T-Test and Test 3 (Hotteling's T2 Test) were used in experimental research and hypothesis testing. From the first hypothesis test, the Sig value was produced. 0.068> 0.05, which means that there is no effect of learning with a combination of the Number Head Together - Debate Method and learning without treatment on student learning activity. While the results of the second Hypothesis test show a Sig value. 0.416> 0.05, namely there is no effect of learning with a combination of the Number Head Together - Debate Method on student self-confidence. And the results of the Hotteling T2 test show that the ρ-value for learning activity is 0.342 > 0.05, meaning that there is no difference in the average learning activity between students from both classes. The ρ-value for self-confidence is 0.049 < 0.05, meaning that there is a difference in the average self-confidence between students from both classes.